Rehabilitation and Biomarkers of Stroke Recovery: Study Protocol for a Randomized Controlled Trial - Picelli, Alessandro; Filippetti, Mirko; Del Piccolo, Lidia; Schena, Federico; Chelazzi, Leonardo; Della Libera, Chiara; Donadelli, Massimo; Donisi, Valeria; Fabene, Paolo Francesco; Fochi, Stefania; Fonte, Cristina; Gandolfi, Marialuisa; et al. (Frontiers in Neurology, 2021)
BACKGROUND. Stroke is a leading cause of disability. Nonetheless, care pathway for stroke rehabilitation takes partially into account the needs of chronic patients. This is due in part to the lack of evidence about the mechanisms of recovery after stroke, together with the poor knowledge of related and influencing factors. Here, we report about the study protocol “Rehabilitation and biomarkers of stroke recovery”, which consists of 7 work-packages and mainly aim to investigate the effects of long-term neurorehabilitation on stroke patients and to define a related profile of (clinical-biological, imaging, neurophysiological, and genetic-molecular) biomarkers of long-term recovery after stroke. The work-package 1 will represent the main part of this protocol and aims to compare the long-term effects of intensive self-rehabilitation versus usual (rehabilitation) care for stroke. METHODS. We planned to include a total of 134 adult sub-acute stroke patients (no more than 3 months since onset) suffering from multidomain disability as a consequence of first-ever unilateral ischemic stroke. Eligible participants will be randomly assigned to one of the following groups: intensive self-rehabilitation (based on the principles of “Guided Self-Rehabilitation Contract”) versus usual care (routine practice). Treatment will last one year and patients will be evaluated every 3 months according to their clinical presentation. The following outcomes will be considered in the main work-package: Fugl-Meyer assessment, Cognitive Oxford Screen Barthel Index, structural and functional neuroimaging, cortical excitability, motor and somatosensory evoked potentials DISCUSSION. This trial will deal with the effects of an intensive self-management rehabilitation protocol and a related set of biomarkers. It will also investigate the role of training intensity on long-term recovery after stroke. In addition, it will define a set of biomarkers related to post-stroke recovery and neurorehabilitation outcome in order to detect patients with greater potential and define long-term individualized rehabilitation programs. TRIAL REGISTRATION. NCT04323501